Knowledge representation for health-care ECAI 2010 workshop KR4HC 2010, Lisbon, Portugal, August 17, 2010 : revised selected papers - KR4HC (Workshop) 2010 Lisbon, Portugal); Riaño, David; Teije, Annette ten.; Miksch, Silvia; Peleg, Mor.; SpringerLink (Online service). (Berlin Springer, 2011)
This book constitutes the proceedings of the KR4HC 2010 workshop held at ECAI in Lisbon, Portugal, in August 2010. The 11 extended papers presented were carefully reviewed and selected from 19 submissions. The papers cover topics like ontologies, patient data, records, and guidelines, and clinical practice guidelines.
Electronic reproduction.
Keywords: Health services administration -- Information technology -- Congresses; Medicine -- Data processing -- Congresses; Machine learning -- Congresses; Artificial intelligence -- Medical applications -- Congresses; Electronic books